Transitioning to Blended Learning: Understanding Student and Faculty Perceptions - Napier, Nanette P.; Dekhane, Sonal; Smith, Stella (Online Learning, 2011)
This paper describes the conversion of an introductory computing course to the blended learning model at a small, public liberal arts college. Blended learning significantly reduces face-to-face instruction by incorporating rich, online learning experiences. To assess the impact of blended learning on students, survey data was collected at the midpoint and end of semester, and student performance on the final exam was compared in traditional and blended learning sections. To capture faculty perspectives on teaching blended learning courses, written reflections and discussions from faculty teaching blended learning sections were analyzed. Results indicate that student performance in the traditional and blended learning sections of the course were comparable and that students reported high levels of interaction with their instructor. Faculty teaching the course share insights on transitioning to the blended learning format.